Peningkatan Kreativitas Santri melalui Pembuatan Kaligrafi dan Pelatihan Digital Marketing di Pondok Pesantren “Al-Munjiyah Durisawo” Ponorogo - Faruq Ahmad Futaqi; Hamida Faza Fadya (Amaluna: Jurnal Pengabdian Masyarakat, 2022)
Pondok Pesantren Al Munjiyah is a women's islamic boarding school located on Jl. Lawu No. 4 Gg. IV Durisawo, Nologaten, Ponorogo which has formal educational institutions MA YP KH Syamsuddin and MTs YP KH Syamsuddin Durisawo Ponorogo. Students of Al Munjiyah Islamic boarding schools regularly participate in various calligraphy competitions and got championships at both district and provincial levels. However, the achievements obtained are only as a point of pride and are not developed into a skill. In fact, with the potential expertise possessed by these students, they can develop it into a business. Businesses in this digital era must also keep up with the trends that exist in society, namely by using digital or internet-based marketing strategies. Departing from the potential and assets of students who have expertise in the field of calligraphy, creating a calligraphy community and making a digital marketing training to increase the creativity of these students is feasible. After the training was carried out, the enthusiasm of the students who had been gathered at the calligraphy business community forum was extraordinary, as well as they were enthusiastic about participating in the training from beginning to end. The monitoring results showed that the ability of the trainees increased. And of course, comprehensive monitoring and evaluation are needed on an ongoing basis in the future.